The effectiveness of transnational non-state governance: The role of domestic regulations and compliance assessment in practice - Olga Malets (Max Planck Institute for the Study of Societies, 2013)
The paper examines how a domestic institutional environment and third-party compliance assessment shape the effects and effectiveness of certification and labeling. Certification represents a form of transnational non-state market-driven governance of the environmental and social performance of firms. Based on an extensive qualitative analysis, this paper explores two factors that influence the forest certification program of the Forest Stewardship Council. First, the institutional setup and the implementation and enforcement of domestic law can restrict the effectiveness of certification if certification requirements contradict or significantly exceed national law or the institutional environment presents significant challenges to certification. Second, I show that third-party auditing, auditors, and certifiers play a crucial role in this challenging institutional environment. I adopt a dynamic approach to the analysis of these elements, focusing on how domestic law and institutions and transnational standards interact over time. Contrary to existing literature, which emphasizes certification and auditing methods and procedures, it is not only how the assessment system is set up but the ways it is applied in practice that shape the implementation of voluntary certification standards and induce certified forestry operations to modify their practices. – – Wirkung und Effektivität von Zertifizierung und Kennzeichnung sind mit dem nationalen institutionellen Umfeld und der externen Bewertung von Compliance verknüpft. Zertifizierung ist eine Form transnationaler, nicht marktgesteuerter Governance der Nachhaltigkeit und Sozialverträglichkeit von Wirtschaftsunternehmen. Auf der Basis einer umfangreichen Qualitätsanalyse untersucht diese Studie zwei Faktoren, die das Waldzertifizierungsprogramm des Forest Stewardship Council beeinflussen. Zum einen können die institutionellen Voraussetzungen sowie Implementierung und Anwendung nationaler Gesetzgebung die Effektivität der Zertifizierung einschränken, wenn ihre Anforderungen den nationalen gesetzlichen Bestimmungen zuwiderlaufen, sie überschreiten oder das institutionelle Umfeld die Zertifizierung erschwert. Zum anderen spielen externes Audit, Auditoren und Zertifizierer eine wichtige Rolle in diesem komplexen institutionellen Umfeld. Mit einer dynamischen Herangehensweise wird analysiert, wie nationale Gesetzgebung, Institutionen und transnationale Standards über längere Zeiträume interagieren. Im Gegensatz zur vorliegenden Literatur, die Zertifizierung, Audit-Methoden und Prozeduren bestätigt, kommt die Autorin zu dem Schluss, dass nicht nur der Aufbau des Zertifizierungssystems, sondern die Art und Weise seiner Anwendung in der Praxis eine Wirkung auf die Implementierung freiwilliger Zertifizierungsstandards und die Einführung zertifizierter Vorgänge in Waldbetrieben haben können.
Keywords: 300